Odpowiedzialność karna syndyka za szkodliwe nadużycie zaufania - Bogajewska, Maria (My University, 2013)
Przedmiotem rozprawy jest analiza pozycji prawnej syndyka na gruncie prawa karnego oraz odpowiedzialności karnej syndyka. Na gruncie polskiego prawa upadłościowego i naprawczego nie mamy żadnych postanowień dotyczących odpowiedzialności karnej syndyka. Odpowiedzialność karna syndyka została omówiona na gruncie art. 231 k.k. (przestępstwo nadużycia władzy) oraz na gruncie art. 296 k.k. (przestępstwo niegospodarności).

The subject matter of the dissertation is an analysis of the position of the trustee in bankruptcy under criminal law and of the basis of his criminal liability. There are no decisions concerning penal liability of a general receiver adjudicated on the grounds of the Polish bankruptcy regulations and restructuring law. The author presents the basis of the trustee in bankruptcy's liability under Article 231 of the Criminal Code (abuse of powers) and Article 296 of the Criminal Code (abuse of functions).
General receiver's penal liability for detrimental activity
Wydział Prawa i Administracji
Keywords: odpowiedzialność karna syndyka; general receiver's penal liability; nadużycie władzy; malfeasance in office; przestępstwo niegospodarności; abuse of confidence; syndyk; general receiver